Physicochemical Characterization of Silver Sulfadiazine in Polymeric Wound Dressings - de Melo, Demis F.; Guedes, Gabryella Garcia; de Carvalho Moreira, Lívia M. C.; Oshiro-Jünior, João Augusto; de Lima Damasceno, Bolívar Ponciano Goulart (Current Pharmaceutical Design, 2023)
The insertion of topical antimicrobials in wound treatment represented an important role in patient management. Among these agents, silver sulfadiazine (AgSD), introduced in the therapy of wounds and burns in the 1960s, is considered the gold standard in treatment due to its mechanism of action, in addition to its proven efficacy and safety. The association of AgSD with polymers for the development of curative formulations has been reported. The evaluation of the physical-chemical properties of these systems with the aid of analytical techniques of characterization is essential for the determination of their activities, besides allowing the detection of possible incompatibilities between AgSD and polymers. Thus, this review presents the main techniques of physicochemical characterization used in the evaluation of systems containing AgSD with curative purposes in order to provide parameters to ensure the efficacy and safety of these new therapeutic options. Microscopic, thermoanalytical, and spectroscopic techniques, for example, provide information on system properties such as surface chemical composition, crystallinity, morphology, and thermal stability of curative formulations containing AgSD. These techniques are important in the selection of the most appropriate techniques during the development of a polymeric curative system containing AgSD, in addition to providing information for cost reduction of a possible scale-up and the establishment of methodologies for quality control of these systems to ensure their efficacy and safety.
Keywords: Wounds